Leaching of Chalcopyrite Concentrate with Hydrogen Peroxide and Sulfuric Acid in an Autoclave System - Turan, M. Deniz; Altundogan, H. Soner (Springer, 2013)
In this study, leaching of chalcopyrite concentrate was investigated in an autoclave system using hydrogen peroxide and sulfuric acid. By decomposition of hydrogen peroxide, the active oxygen formed can provide both high oxidation potential and high pressure in a closed vessel for leaching. Preliminary studies showed that hydrogen peroxide can be used as an oxidant instead of oxygen gas in the autoclave. Central composite design (CCD) was used to examine the effects of the experimental parameters on the copper and iron extraction as a response. The proposed model equation using CCD showed good agreement with experimental data, the correlation coefficients R (2) for copper and iron being 0.84 and 0.86, respectively. The optimum conditions to obtain the main goal of maximum copper and minimum iron extraction from chalcopyrite were determined as to be sulfuric acid concentration of 2.5 M, hydrogen peroxide concentration of 2.3 M, leaching time of 24 minutes, chalcopyrite amount of 3.17 g (in 50-mL solution), stirring speed of 630 rpm, and leaching temperature of 351 K (78 A degrees C). Under the optimum condition, 76 pct of copper and 9 pct of iron were extracted from chalcopyrite concentrate. Extraction yield results of metals indicate that selective leaching of chalcopyrite can be achieved using hydrogen peroxide and sulfuric acid in an autoclave system.
Keywords: Dissolution Kinetics; Ferric Ion; Part Ii; Copper; Pressure; Chlorination; Sulfidation; Sphalerite; Recovery